Business Incubator Organizational Communication Patterns In Efforts to Empower MSMEs in Lampung Province - Azizah, Tazkiyah; Luqman, Yanuar (Universitas Islam Negeri Raden Intan Lampung, 2023)
Siger Innovation Hub (Sigerhub) is a business incubator that impacts efforts to develop the potential of MSMEs in Lampung Province. Sigerhub has various coaching programs such as talent hub, incubation, funding & market access, which are presented as